Estimating the Effectiveness of Fiscal Policy in stimulating Economic Activity in Low-Income Countries: A Case Study of Uganda - Masiko Bakainaga Niwagaba (Uganda Christian University, 2023)
The relationship between the business cycle and government policy is at the core of economics regardless of which school of thought an economist subscribes to. More recently a large magnitude of economic shocks has been seen which have induced government intervention. With this the size of governments has risen drastically, eliciting greater debate on the necessity of large government budgets. This paper characterises the dynamic effects of shocks in government spending and taxes on economic activity in Uganda in the period between 2000-2020. It approaches this by using a structural vector autoregression study approach. It endeavours to estimate the size of fiscal and tax multipliers through this method, using secondary data capturing measurements of economic indicators for Uganda. Objective One, determining the size of the multiplier effect of government expenditure, revealed that there are small but positive effects that government expenditure has on stimulating economic activity. The coefficient for the lagged value for government expenditure on current income (GDP) was found to be 0.198. This means that for every 1 unit increase in government expenditure, there is a correspondent 0.198 increase in GDP. This goes against conventional Keynesian economics of the fiscal multiplier, which asserts that increases in net government expenditure raises the total GDP by more than the amount of the increase. It has been found here that the multiplier effect is less than 1 for government expenditure, while it is -0.3 for tax multiplier. Objective Two, which examined the government’s ability to impact an economy’s business cycle through expenditure. Through the Impulse Response Function, it can be seen how GDP would respond to an unexpected shock in government expenditure or taxation, as it traces the dynamic impact to a system of a “shock” or change to an input. The Impulse Reaction Functions reveal that in the immediate term changes in government and tax do not have very large impact, but as time increases the impact gradually increase. This shows that changes in fiscal policy are not the only Objective Three aimed to establish the ideal fiscal policy stance based on the results of the study. This conclusion is arrived at by considering the results of the two prior objectives. Given that multipliers are small and do not have substantial impact on the business cycle. It is ideal for government to adopt a laissez faire policy stance. This is one where government tends not to intervene in the market limiting the government expenditure in order to prop up the economy. However, in order to fix the existing budgetary deficit, it is ideal that government increase taxation in order to return to a surplus. In conclusion, this research offers great insight into the fiscal policy in developing countries. It shows that impact of expansionary fiscal policy does not have as great an impact as expected, this could be because of the impact of rational expectations. As government increases in size, the private sector sees this and shrinks in size in order to accommodate the government. This is why government expenditure is often inefficient in impacting the business cycle and large amounts are required in order to stabilize the country.
This is a dissertation.